Planificación estratégica y su relación con la calidad de los servicios a los usuarios de la empresa eléctrica CNEL EP del cantón Vinces provincia de los Ríos - Grefa Tovar, Martha Narcisa (2018)
This investigation was carried out in the electrical company CNEL EP of the province of Vinces province of Los Ríos. On strategic planning and its relationship with the quality of services to users For the purpose of this research, the problem tree is elaborated in relation to the negative problem posed, in which the causes and the possible effects were pointed out. An extensive bibliographical consultation was carried out, consultation in the web pages and experts in the subject where a substantial information was found that was selected and validated to structure the theoretical framework. Then the survey was applied to the different secretaries and heads of the institution, and an observation guide was applied to control the processes that were carried out. After carrying out the processes, it was possible to verify the results that showed that the secretaries do not update their knowledge nor have they updated the computer programs of the computers.